The Effect of Fermented Shallot Skin on The Growth Of Muscle Plants (Brassica Juncea) - Waris Waris; Hasni Ummul Hasanah; Raudhatul Hasanah (PROGRAM STUDI PENDIDIKAN BIOLOGI, 2021)
Shallot skin is a kitchen waste that contains good nutrients for plant growth. Shallot skin contains calcium, phosphorus, and iron. The fermented shallot skin has nutrients N-total 1.29%, C-organic 17.32%, P2O5-total 0.46%, K2O-total 0.70%, and so on. This study aims to determine the effect of shallot skin fermentation on the growth of mustard (Brassica juncea) plants. This research was conducted using a Randomized Block Design method consisting of 6 treatments and 4 replications, including; P0 (without fertilizer as negative control), P1 (inorganic fertilizer as positive control), P2 (25 gr), P3 (50 gr), P4 (75 gr), and P5 (100 gr). The observed growth parameters include; plant height, number of leaves, wet weight, and leaf area of ​​mustard plants. The data obtained were analyzed using Anova analysis at a 95% confidence level, then further tested with Duncan's test. The results of this study showed that the application of organic fertilizer from the fermented shallot skin had a significant effect on the parameters of plant height, number of leaves, and wet weight, but had no significant effect on leaf area of ​​mustard plants. Treatment of organic fertilizer from shallot skin at a dose of 25 grams can replace the application of inorganic fertilizer (urea) on all parameters, except for leaf area.